Curso de capacitação para professores do ciclo I na área de língua portuguesa: teorias e práticas de aprendizagem - Luna, Tânia Souza de (2008)
This research has its origin in several discussions about learning of reading, writing and pedagogical practices from teachers of elementary school.The study intends to answer how a training course helps pedagogical practices and how it makes teachers of elementary school change their teaching practices in the present schools. Then, first of all we think our reality is complex and it creates a lot of meanings so schools need training their students for living actively in society. It is important to discuss how schools teach knowledge about linguistics associated to social practices. So we associated theory and practices (conceptions of learning, language and literacy) because pedagogical practices need to be led by clear objectives and to be a connection between society and people. For statistical analysis, we have made a survey with training teachers by a program of training teachers called Letra e Vida from Secretaria de Educação do Estado de São Paulo. This research aims to contribute to discussions about learning and literacy in public schools